Assessment of Reading Literacy and Text Handling Knowledge of 4th Grade Students Based on the PIRLS Program - Sheralikizi, Ibragimova Khurshida (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the purpose of reading literacy in the PIRLS international assessment program and the criteria for assessing questions and assignments on the texts used in the study. It also discusses the importance of research and working with texts in an elementary 4th grade textbook as part of the research.